Estudos Físico-Químicos do corante Eritrosina B e seus derivados ésteres visando aplicações fotodinâmicas - Pellosi, Diogo Silva (2012)
The excitation of a photosensitizer dye (PS) with visible light in the presence of oxygen leading to the formation of cytotoxic species (such as singlet oxygen) is the principle of two photochemical treatment modalities known as photodynamic therapy (PDT) and photodynamic inactivation of microorganisms (PDIMO). The xanthenic dye erythrosine has several important properties of a photosensitizer for photodynamic applications, but its low hydrophobicity decreases its association for membranes. The insertion of alkyl chains to the dye can increase its affinity for membrane model systems, evaluated here by micellar systems. We studied erythrosin (ERI) and its ester derivatives named as methyl (ERIMET), buthyl (ERIBUT) and decyl (ERIDEC) in aqueous environment and in aqueous anionic (SDS), cationic (CTAB) and nonionic (P-123)micelles. We evaluated their acid-base equilibria, hydrophobicity, binding and localization in micellar environments and photophysical properties as quantum yield of fluorescence and singlet oxygem formation, and the application in microorganisms. The synthesis of ester derivatives of erythrosin were quick and relatively easy to reproduce, with high yields and purity. The protolitic and tautomeric system of ERI is very complex and dependet of the medium where the dye is located. With the analysis of the data set (by multivariate methods) and comparisons with their ester derivatives was possible attribute the ERI pKa. Even an unexpected effect of reversing the acidity of the phenol and carboxylic acid group was detected in micelles and confirmed by studying mixtures of water-DMSO. The hydrophobicity of the dyes was evaluated by its partition between the system 1-octanol/water. It was observed that the insertion of the alkyl chain increased the hydrophobicity of the dye, and thus its affinity for membanes. The micellar environments studied affects significantly the absorption and mission spectra of these dyes. Such changes are related to the different dieletric constant and polarity in the micellar micro-environment. We evaluated the importance of x hydrogen bonding on their photophysical properties through the use of organic solvents, showing strong solvation by protic solvents. The binding constants and localization determined by fluorimetry were consistent with the charge and hydrophobic characteristics of the dyes and micelles. The order of the binding constants was ERIDEC > ERIBUT > ERIMET > ERI in all micelles. CTAB micelles showed a biphsic interaction due to the association of cationic monomers and anionic dyes. The fluorescence quantum yield increases in the presence of micelles, but still has a relatively small value. The quantum yields of singlet oxygem is high in all cases and are similar to each other independent of the dyes evaluated. The experiments on S. Aureus showed that ERI and ERIMET are effective in inactivating Gram-positive microorganisms showing that this PS are possible to apply both in PDT as in PDIMO.